VdAHA1 positively regulate pathogenicity in Verticillium dahliae - Li, Dongpo; Yuan, Yuan; Zhou, Jinglong; Feng, Zili; Wei, Feng; Zhu, Heqin; Zhao, Lihong; Feng, Hongjie; Zhang, Yalin (Frontiers in Microbiology, 2025)
AHA1 (activator of HSP90 ATPase) is a co-chaperone protein that mainly performs its function by interacting with the HSP90. The biological function of AHA1 has been widely reported in many species. In this study, we knocked out the VdAHA1 gene of V. dahliae by homologous recombination method. The VdAHA1 knockout mutants showed increased drug sensitivity to ergosterol synthesis pathway, significantly inhibiting ergosterol biosynthesis. The VdAHA1 knockout mutant strain also showed decreased melanin in microsclerotia by reduced expression of microsclerotia and melanin related genes Vaflm, Vayg1, and VdSCD. The VdAHA1 mutant showed decreased conidial production that were slightly damaged and showed more sensitivity to abiotic stresses such as temperature, SDS, CR, Sorbitol (SBT), NaCl, and KCl and decreased ATP contents. More importantly, the mutant was significantly less virulent to cotton than the wild type. This study identified the important functions of VdAHA1 in the growth, stress resistance, and virulence.